The BC Carbon Tax : Consumer Response to an Environmental Gasoline Tax - Guenther, Grant (Université d'Ottawa | University of Ottawa, 2013)
I show that the carbon tax in BC, imposed in July 2008 caused a decline in gasoline demand. Furthermore, the carbon tax caused a larger decline in demand than would otherwise be caused by an equivalent price increase in oil prices or other excise taxes. Once the initial shock in demand that occurs following the introduction of the carbon tax is accounted for, subsequent increases to the carbon tax result in a decrease in gasoline demand similar to an equivalent increase in gasoline prices. Unit root tests are also performed on the variables used in regressions. Reductions in gasoline consumption and CO2 emissions as a result of the carbon tax are also calculated